Toward a Script Theory of Guidance in Computer-Supported Collaborative Learning - Fischer, Frank; Kollar, Ingo; Stegmann, Karsten; Wecker, Christof (Educational psychologist, 2013)
This article presents an outline of a script theory of guidance for computer-supported collaborative learning (CSCL). With its 4 types of components of internal and external scripts (play, scene, role, and scriptlet) and 7 principles, this theory addresses the question of how CSCL practices are shaped by dynamically reconfigured internal collaboration scripts of the participating learners. Furthermore, it explains how internal collaboration scripts develop through participation in CSCL practices. It emphasizes the importance of active application of subject matter knowledge in CSCL practices, and it prioritizes transactive over nontransactive forms of knowledge application in order to facilitate learning. Further, the theory explains how external collaboration scripts modify CSCL practices and how they influence the development of internal collaboration scripts. The principles specify an optimal scaffolding level for external collaboration scripts and allow for the formulation of hypotheses about the fading of external collaboration scripts. Finally, the article points toward conceptual challenges and future research questions.